2011
DOI: 10.1111/j.1748-5827.2011.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposuction for removal of lipomas in 20 dogs

Abstract: Liposuction may be less invasive and more attractive to owners than conventional surgery for lipomas up to 15 cm in diameter. Liposuction is not recommended for infiltrative or giant inguinal lipomas. Regrowth can be expected in a high proportion of lipomas, which should be considered when choosing liposuction over conventional excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…27 Furthermore, lipomas bigger than 15 cm have a higher risk of developing seroma and the reported recurrence is high (28%). 27 In one study, radiation therapy alone or in combination with surgery was beneficial for 12 out of 13 dogs, but numbers were too small in this report. 26 Single studies reported the use of subcutaneous deoxycholate injections and the use of a subdermal 1064-nm Nd: YAG laser, but large-based studies are needed to validate these techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Furthermore, lipomas bigger than 15 cm have a higher risk of developing seroma and the reported recurrence is high (28%). 27 In one study, radiation therapy alone or in combination with surgery was beneficial for 12 out of 13 dogs, but numbers were too small in this report. 26 Single studies reported the use of subcutaneous deoxycholate injections and the use of a subdermal 1064-nm Nd: YAG laser, but large-based studies are needed to validate these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…4 Liposuction represents an effective way to remove small, well-defined lipomas but the absence of discrete lobules and the tendency to interdigitate muscle fibres makes it not suitable to treat infiltrative lipomas. 27 Furthermore, lipomas bigger than 15 cm have a higher risk of developing seroma and the reported recurrence is high (28%). 27 In one study, radiation therapy alone or in combination with surgery was beneficial for 12 out of 13 dogs, but numbers were too small in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive liposuction of a giant lipoma in one dog [17], and irradiation of infiltrative lipomas in 13 dogs have been reported [18]; however, these procedures require general anaesthesia and special devices. In a recent retrospective study of 20 dogs, dry liposuction was effective in preventive the growth of existing lipomas less than 15 cm in diameter, while giant lipomas associated with fibrous trabeculae could not be easily removed and attempts at removal resulted in a high risk of bruising, hematoma and seroma; furthermore, regrowth of tumours was observed in 28% of lipomas treated with liposuction at follow-up between 9 and 36 months [19].…”
Section: Introductionmentioning
confidence: 99%
“…For medium (4-10 cm) to large (>10 cm) lipomas, liposuction has been shown to be a minimally invasive technique that provides excellent cosmetic results. [1][2][3][4][5][6] To prevent recurrences, the lipoma's Þ brous capsule is extracted after liposuction, using the slit-incision entry site of the liposuction cannula. Although surgical excision allows for a facilitated extraction of the entire lipoma, extraction of the Þ brous capsule through a slit incision is very difÞ cult.…”
mentioning
confidence: 99%